Relative permeability model of polymer particle dispersed phase for oil displacement based on fractal theory - CUI Chuanzhi, SUI Yingfei, WANG Yidan, WU Zhongwei, LI Jing (Youqicang pingjia yu kaifa)
In the later stage of water injection development, the rapid increase in water content significantly degrades the development performance of water drive reservoirs. The non-uniform distribution and viscosity enhancement of polymer particle dispersed systems effectively reduce the water phase flow capacity that occupies the flow space of large pores, thereby mitigating inefficient and ineffective water circulation. Currently, studies on polymer particle dispersed phase for oil displacement are primarily based on laboratory simulations, focusing on the migration behavior of polymer particles. However, limited research has been conducted on the oil-water flow dynamics and relative permeability curves during the oil displacement process of polymer particle dispersed phase. This study first analyzed the non-uniform distribution of polymer particles in porous media and introduced the red blood cell dendritic volume fraction distribution theory from biological fluid dynamics. A viscosity characterization method was established, considering the effects of the polymer particle phase separation mechanism. Subsequently, a relative permeability model of polymer particle dispersed phase for oil displacement was developed based on fractal and percolation theories. The accuracy of the model was validated through comparisons with laboratory core displacement experiments, and the effects of various factors on the relative permeability of polymer particle dispersed phase for oil displacement were analyzed. This research holds significant value for assessing the development performance of polymer particle dispersed phase for oil displacement.